Análisis de los efectos socioeconómicos del desempleo en el Ecuador: repercusiones en la pobreza, periodo 2011-2021. - Dumas Coraisaca, Mayerly Madelaine; Ramirez Chavez, Leslie Nicole (Machala : Universidad Técnica de Machala, 2024)
Unemployment in Ecuador is a problem that affects the population, which contributes significantly to poverty and the precariousness of the quality of life. Governments implement labor programs and reforms to address this situation, while government agencies such as the National Institute of Statistics and Census (INEC) collect data on unemployment rates. Notably, the pandemic exacerbated the problem, causing mass layoffs due to the lack of economic income to maintain workers' salaries during periods of confinement. The findings reveal that unemployment not only affects income and working conditions, but also deepens poverty and social exclusion. Key moments are identified, such as the increase in unemployment in 2016 due to an earthquake and its increase during the pandemic in 2020. The research underlines the need to comprehensively address unemployment through policies that promote job creation and strengthen social protection. In addition, it highlights the importance of understanding the dynamics between unemployment and poverty in order to inform future research and the development of more effective strategies.
El desempleo en Ecuador es una problemática que afecta a la población, lo que contribuye significativamente a la pobreza y la precarización de la calidad de vida. Los gobiernos implementan programas y reformas laborales para hacer frente a esta situación, mientras que agencias gubernamentales como el Instituto Nacional de Estadística y Censos (INEC) recopila datos sobre las tasas de desempleo. Cabe destacar que la pandemia exacerbó el problema, causando despidos masivos debido a la falta de ingresos económicos para mantener los salarios de los trabajadores durante los períodos de confinamiento. Los hallazgos revelan que el desempleo no solo afecta los ingresos y las condiciones laborales, sino que también profundiza la pobreza y la exclusión social. Se identifican momentos clave, como el aumento del desempleo en 2016 debido a un terremoto y su incremento durante la pandemia de 2020. La investigación subraya la necesidad de abordar integralmente el desempleo mediante políticas que promuevan la creación de empleo y fortalezcan la protección social. Además, destaca la importancia de comprender la dinámica entre el desempleo y la pobreza para informar futuras investigaciones y el desarrollo de estrategias más efectivas.
Keywords: DESEMPLEO; POBREZA; INGRESOS ECONOMICOS; PANDEMIA